Characteristic and bioactivities value of Nypa fruticans from coastal area in West Aceh District, Indonesia as a candidate antidiabetic agent - YULIA FITRI; YUSNI YUSNI; TAUFIK SURYADI; MUDATSIR MUDATSIR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fitri Y, Yusni Y, Suryadi T, Mudatsir M. 2023. Characteristic and bioactivities value of Nypa fruticans from coastal area in West Aceh District, Indonesia as a candidate antidiabetic agent. Biodiversitas 24: 5260-5269. Nypa fruticans Wurmb is a functional plant that grows on the coasts of Indonesia, produced food and has health benefits. It has been believed for generations that Nypa fruticans Wurmb has potential as an antidiabetic, although a complete study is needed. This research aimed to evaluate the potential of the fruit of the Nypa fruticans Wurmb plant as an antidiabetic based on its characteristic values and pancreatic histopathology. The fruit was evaluated for phytochemical, tannin quantity, chemical compound determination, and confirmation of bioactivity. Antidiabetic properties were evaluated for pancreatic histopathology in an animal model. Nypa fruticans Wurmb contains polyphenols, tannins, saponins, triterpenoids, alkaloids and flavonoids, with a tannins quantity of 11.10 mg/AT/g extract. Furthermore, it contains antioxidant, and anti-inflammatory compounds, including the dominant 2,3-Butanediol (CAS) Butane-2,3-diol, Propane-1,1-diol diacetate, 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydrox, and 9,12-Octadecadienoic acid (Z,Z)- (CAS) Li. In addition, it has excellent bioactivity against nuclear receptor ligands, protease inhibitors, and enzyme inhibitors as an indicator of binding affinity with hot cells. Nypa fruticans Wurmb can increase beta cells, and expand the islets of Langerhans. The Nypa fruticans Wurmb, besides containing antioxidant and inflammatory compounds, has hight bioactivity, wich increases the frequency of beta cells and improves pancreatic islets of Langerhans repair in diabetic models.